Xenotransplantation : Comprehensive Study - Miyagawa, Shuji; Miyagawa, Shuji (IntechOpen, 2020)
Recently, remarkable progress has been made in the area of preclinical xenotransplantation experiments. Surprisingly, a heterotopic heart from the gene-editing pig continued to beat for almost 2.5 years, when implanted in the monkey abdomen, and a pig life-supporting kidney could also function for over 1.3 years in monkeys. Concerning islets, islets from gene-editing pigs could work for more than one year in monkeys. It is noteworthy that one group reported a survival of adult wild-type pig islets of over 600 days. On the other hand, the progress in these preclinical trials strongly affected not only the xenotransplantation study itself but regeneration studies to use pigs as a scaffold to foster human induced pluripotent stem cells.
English
Keywords: Biomedical engineering; Biomedical engineering